Profil Pembelajaran Berdeferensiasi Berorientasi ESD pada Materi Ekologi dan Keanekaragaman Hayati di SMP N 1 Wirosari Kabupaten Grobogan - Erlinawati, Banundari; Dewi, Endah Rita Sulistya; Nugroho, Ary Susatyo; Roshayanti, Fenny (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The aim of this research is to obtain an overview of the use of ESD-oriented differentiated learning in science learning Ecology and Biodiversity material at SMP N 1 Wirosari, Grobogan Regency. Currently differentiated learning is very necessary in the Merdeka curriculum, because by using differentiated learning a teacher can find out students' readiness to receive lessons and find out students' heterogeneous learning styles. Education for Sustainable Development (ESD) is defined as education that encourages change in knowledge, skills, values and attitudes to enable a more sustainable and equitable society for all. The type of research used is field research. The data collection techniques used were observation, questionnaires, interviews and documents. The data analysis technique uses qualitative description techniques with a sample of 2 science teachers at SMPN 1 Wirosari, Grobogan district